2020
DOI: 10.3390/medicina56080390
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Selected Demographic Factors and Speech Organ Dysfunction in Sporadic ALS Patients

Abstract: Background and objectives: Speech disorders are observed in 30% of newly diagnosed sporadic amyotrophic lateral sclerosis (ALS) patients. Characterized by a dynamic course, dysfunction of articulation has not so far been well understood. The aim of this study was to analyze the influence of demographic factors (sex, age, duration of the disease) and concomitant diseases (degenerative spine disease, depression, hypertension, hypothyroidism, hyperthyroidism, and allergy) on the functioning of speech organs in AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…They found substantial regional variations in the prevalence of cardiovascular conditions [170]. Hypertension was highest in France (57%) [171], Portugal (48%) [172,173], while the Netherlands [174] and Poland [175] reported lower rates at approximately 26% and 23% respectively. Chinese ALS patients had even lower prevalence of hypertension at 15% [176].…”
Section: Cardiovascular Comorbidities In Alsmentioning
confidence: 99%
“…They found substantial regional variations in the prevalence of cardiovascular conditions [170]. Hypertension was highest in France (57%) [171], Portugal (48%) [172,173], while the Netherlands [174] and Poland [175] reported lower rates at approximately 26% and 23% respectively. Chinese ALS patients had even lower prevalence of hypertension at 15% [176].…”
Section: Cardiovascular Comorbidities In Alsmentioning
confidence: 99%
“…Speech disorders arise from bulbar involvement, leading to changes in four areas: articulation, respiration, phonation, and resonance [ 3 ]. It has been shown that speech deterioration associated with the length of phonation and voice loudness is more dynamic in men [ 4 ]. Changes occurring in these areas have serious consequences on the functioning of patients with ALS.…”
Section: Introductionmentioning
confidence: 99%